Evaluation of Eurostat education, training and skills data sources - (:unkn) unknown (Office for Official Publications of the European Communities, 2008)
"Adequate and consistent data are the key to understanding what is happening in vocational education and training (VET).The harmonised data sources of the European statistical system provide the core of relevant data according to commonly agreed quality standards. Yet currently available data sources do not provide a comprehensive and consistent picture of developments in education, training and skills, especially for VET. This publication takes stock of the VET data available from current and planned Eurostat surveys and data collections. It provides a clear picture of the current and future scope of VET statistics, important methodological issues for comparing and combining different data sources and short, medium and long-term visions of improvements." (Hrsg, BIBB-Doku)
Keywords: T 3.5 Statistik; S 3.5.5.1 CEDEFOP; I 2.2 Europa; Berufsbildungsstatistik; CEDEFOP